A CASE STUDY OF ECOTOURISM POTENTIAL IN KALSUBAI PEAK (International Journal of Food and Nutritional Sciences, 2022)
Kalsubai is the highest peak in Maharashtra with altitude of 1646 mts from mean sea level. It is one of the mountains of the Sahyadri Ranges. Kalsubai is situated on the border of Nashik and Ahmednagar district. Thousands of tourists across Maharashtra visits every year to the Kalsubai Peak for the purpose of ecotourism. The visitors of Kalsubai also have the benefit of a beautiful and largest water reservoir i.e. Bhandardara Dam (Arthur Lake) and magnificent natural waterfall Randha Fall on the Pravara River. The scenenic beauty of the fall, the adventure of trekking, the facility of boating, the beautiful landscape, floral beauty, biodiversity, a wide variety of wildlife mainly birds attract lakhs of tourists every year. The availability of fish food at Bhandardara Dam is one more factor of attraction of these tourists. The community has an advantage of ecotourism interms of tourism, provision of food, hoteling, accommodation, art & crafts, etc